Konstribusi Matematika dalam Pembentukan Karakter Siswa - Rahmi, Rahmi (Prodi Pendidikan Matematika, 2013)
Education is proposed to cause humans to have good personality and characters. The implementation of character education needs whole understanding about the concept of character building and education. Building the studentsâ character is not an easy and simple task, but it needs some serious efforts which should be continuously done. Therefore, government has promoted curriculum based-character from 2010-2014, by which the character education is not only assigned to one of the subjects as Citizenship Education, but also to other subjects including mathematics. Mathematics is one of the subjects supporting the government program of character education, because some character values, as honesty, responsibility, care network, independence, and etc have been integrated in it. Thus, learning mathematics is not only focused on gaining cognitive purposes, but also on gaining affective and psychomotor purposes. In learning process, the teacher character so that the students can put him or her as the rule model.Â Key Word: Character Education